Attachment Styles And Marital Quality Between Spouses - Fatahyah Yahya; Aqilah Yusoff; Ahmad Tarmizi Talib; Sarjit Singh Darshan Singh; Abdul Hakim Mohad; Nur Ayuni Mohd Isa; Muhammad Jazlan Ahmad Khiri (UNIMAS Publisher, 2024)
Indexed by MyCite